Washington University School of Law’s Global Trajectory - Leila Nadya Sadat (Washington University Journal of Law & Policy, 2017)
This Essay discusses the changing nature of legal education, focusing on the movement from national to global law schools, specifically within the context of globalization. Sadat details the development of international and comparative legal education at Washington University and reflects on their benefit to the School’s reputation. Sadat closes with a discussion of “Global Trumpism,” its potential impact on the Pax Americana, and the resulting effect on Washington University’s international and comparative legal education programs.
Keywords: Washington University School of Law; international and comparative law; legal education; international law; Pax Americana; globalization; comparative legal education